Hypoxia on the Expression of Hepatoma Upregulated Protein in Prostate Cancer Cells - Espinoza, Ingrid; Sakiyama, Marcelo J.; Ma, Tangeng; Fair, Logan; Zhou, Xinchun; Hassan, Mohamed; Zabaleta, Jovanny; Gomez, Christian R. (Frontiers in Oncology, 2016)
Hepatoma Up-Regulated Protein (HURP) is a multi-functional protein with clinical promise. This protein has been demonstrated to be a predictive marker for the outcome in high-risk prostate cancer (PCa) patients besides being a resistance factor in PCa. Although changes in oxygen tension (pO2) are associated with PCa aggressiveness, the role of hypoxia in the regulation of tumor progression genes such as HURP has not yet been described. We hypothesized that pO2 alteration is involved in the regulation of HURP expression in PCa cells. In the present study, PCa cells were incubated at 2% O2 (hypoxia) and 20% O2 (normoxia) conditions. Hypoxia reduced cell growth rate of PCa cells, when compared to the growth rate of cells cultured under normoxia (p<0.05). The decrease in cell viability was accompanied by 5-fold (p<0.05) elevated rate of vascular endothelial growth factor (VEGF) release. The expression of VEGF and the hypoxia-inducible metabolic enzyme carbonic anhydrase 9 (CA9) were elevated maximally nearly 61-fold and 200-fold, respectively (p<0.05). Noted in two cell lines (LNCaP and C4-2B) and independent of the oxygen levels, HURP expression assessed at both mRNA and protein levels was reduced. However, the decrease was more pronounced in cells cultured under hypoxia (p<0.05). Interestingly, the analysis of patients’ specimens by Western blot revealed a marked increase of HURP protein (5-fold), when compared to control (cystoprostatectomy) tissue (p<0.05). Immunohistochemistry analysis showed an increase in the immunostaining intensity of HURP and the hypoxia-sensitive molecules, hypoxia-inducible factor 1-alpha (HIF-1a, VEGF, and Heat shock protein 60 (HSP60) in association with tumor grade. The data also suggested a redistribution of subcellular localization for HURP and HIF-1a from the nucleus to the cytoplasmic compartment in relation to increasing tumor grade. Analysis of HURP Promoter for HIF-1 binding sites revealed presence of 4 putative HIF binding sites on the promoter of DLGAP5/HURP gene in the nontranslated region upstream from the start codon, suggesting association between HIF-1a and the regulation of HURP protein. Taken together, our findings suggest a modulatory role of hypoxia on the expression of HURP. Additionally our results provide basis for utilization of tumor–associated molecules as predictors of aggressive PCa.